Developing and Fostering Creativity Through the Works of Art by Young Pupils - Selaković, Kristinka (Revija za elementarno izobraževanje, 2017)
The aim of this experimental research was to examine the effectiveness and impact of active observation of the work of art by applying specially designed strategies, methods and procedures to the development of general artistic creativity in pupils. The research was conducted on a sample of 199 pupils (the experimental group consisted of 102 pupils, and the control group of 97 pupils) from two primary schools in Užice (Serbia). The conclusions indicate how important it is for children to access the work of art on a personal level, independently and through interaction, as well as to develop their own concepts.
Keywords: creativity; work of art; young pupils; development program; museum